Key Aspects of Rehabilitation for Children at Risk - Israilova, Nodira (Special Education, 2022)
This article describes children at risk in the context of a pedagogical problem, analyzes various interpretations of the “rehabilitation” concept in scientific literature and explains the need for rehabilitation work with children in teachers’ practice. On the basis of an empirical review (a questionnaire survey) a spectrum of ideas and opinions of teachers and psychologists from different educational institutions on the goals and objectives of rehabilitation work with children at risk and the main directions for this work in their practical activities have been revealed. In order to analyze the interpretations of specialists’ opinions regarding the nature and assessment of the effectiveness of rehabilitation, a method of collecting qualitative data (questionnaire survey, conversation) with open-ended questions was used. The author summarized the answers of the specialists on the problem under study by the method of content analysis using an open-coding procedure.According to the results of the research, six rehabilitation contexts have been identified, most specialists consider rehabilitation as comprehensive assistance to children with the aim of successfully returning them to a full social life; involving them into the system of social relations in the course of specially organized education; vocational training; developing healthy lifestyle and law-abiding behavior.
Keywords: children at risk; deviant behavior; maladaptation; legal rehabilitation; medical rehabilitation; social and pedagogical rehabilitation; comprehensive assistance and support; professional activities; social adaptation